Efficient synthesis of an aluminum amidoborane ammoniate - Yang, J.; Beaumont, P.; Humphries, Terry; Jensen, C.; Li, X. (2015)
A novel species of metal amidoborane ammoniate, [Al(NH2BH3)6 3-][Al(NH3)6 3+] has been successfully synthesized in up to 95% via the one-step reaction of AlH3·OEt2 with liquid NH3BH3·nNH3 (n = 1~6) at 0 °C. This solution based reaction method provides an alternative pathway to the traditional mechano-chemical ball milling methods, avoiding possible decomposition. MAS 27Al NMR spectroscopy confirms the formulation of the compound as an Al(NH2BH3)6 3- complex anion and an Al(NH3)6 3+ cation. Initial dehydrogenation studies of this aluminum based M-N-B-H compound demonstrate that hydrogen is released at temperatures as low as 65 °C, totaling ~8.6 equivalents of H2 (10.3 wt %) upon heating to 105 °C. This method of synthesis offers a promising route towards the large scale production of metal amidoborane ammoniate moieties.